Sex Differences in In-hospital Mortality of Patients With Septic Shock: An Observational Study Based on Data Analysis From a Cover Sheet of Medical Records in Beijing - Zhou, Xiao; Zeng, Na; Liu, Pei; Liu, Zhuang; Duan, Meili (Frontiers in Medicine, 2021)
Background: The goal of our study was to evaluate the association of sex and in-hospital mortality in patients with septic shock in Beijing, China. Materials and Methods: We analyzed 3643 adult patients with septic shock from January 1, 2019, to Dec 31, 2019, in all secondary and tertiary hospitals in Beijing. Study data were retrospectively extracted from the Quality Control Center of Beijing Municipal Health Commission. Results: There were 2345(64.37%) male and 1298(35.63%)female patients. Compared to male patients, female patients with septic shock had a higher in-hospital mortality rate(55.54% versus 49.29%, p＜0.01).The median length of hospitalization stay for male patients was 22.71 days, while that for female patients was 19.72 days (p>0.01). Male patients had a higher prevalence of pulmonary infection(68.8% versus 31.2%, p＜0.01). The B values of sex in univariate and multivariate logistic regression were -0.251 and -0.312, respectively. Men had a lower likelihood of hospital mortality than women(OR=0.732, 95% CI =0.635-0.844, p=0.000). Conclusions: Female patients with septic shock had a higher risk of dying in the hospital than male patients.